What Factors Explain Postharvest Losses of Orange Fruit (Citrus sinensis) from Farm to Fork in the Tropics? - Obayelu, Oluwakemi Adeola; Dairo, David Olusegun; Olowe, Olukemi Olumuyiwa (Agricultura Scientia, 2022)
Demand for citrus fruit has increased over the years in Nigeria. However, post-harvest loss of tropical fruits is high in developing nations owing to poor handling and storage facilities along the supply chain. The study therefore assessed levels and correlates of postharvest losses of fresh oranges along the orange supply chain. Primary data collected from marketersand producers of orange were analysed using descriptive statistics and ordered logit. Orange farming was dominated by male (68.4%) while orange marketing was dominated by females. Most of the producers (63.16%) and wholesalers (65.38%) experienced postharvest loss of 6-10%, while 46.79% of the retailers experience a postharvest loss of less than 5%. Being a male farmer that harvested oranges in the afternoon increased the likelihood of postharvest losses among the farmers while having a large household size reduced it. However, education, smallholding marketing and use of storage facilities reduced the likelihood of postharvest loss among orange marketers. Postharvest training for farmers and marketers on fruit harvesting and storage methods will help to minimise postharvest loss from producers to retailers.
Keywords: postharvest losses; producers; marketers; ordered probit